Characterization, Thermal and Morphological Analysis of Blanched Pretreated Winged Bean Flour - Riwayati, Indah; Hartati, Indah; Purwanto, Helmy (Journal of Sustainable Materials Processing and Management, 2022)
Legumes are a nutritionally dense food source that is widely consumed throughout the world. Winged bean seeds are one of the constituents of nuts. Apart from their use as a culinary item, winged bean seeds can be utilized as a raw material to manufacture compostable coatings and films that help extend the shelf life of food. Biodegradable coatings and films are intended to have physical and chemical qualities that enable them to perform these purposes. This study aimed to determine the chemical composition, morphology, thermal and infrared spectral of pretreated and raw winged bean flour. Proximate analysis revealed how pretreatment decreases winged bean flour's carbohydrate, protein, fat, and ash content. Throughout this period, the water content increased. Thermogravimetric analysis indicates two primary decomposition processes of pretreated winged bean flour showed prominent peaks at 271 oC and 404.2 oC with mass loss of 42.09 % and 32.95 %, respectively. Morphology analysis revealed that the average diameter of granules is the range value of 5-15 µm for pretreated flour. On the other hand, infrared spectral exhibit polysaccharide in pretreated flour is expressed as 1,4 glycosidic linkages, amide I and amide II at bands 1161 cm-1,  1647 cm-1, and 1541 cm-1, respectively.